Anopheles stephensi and the risk of increased urban malaria in South Africa - Maria L. Kaiser; Yael Dahan-Moss; Lizette L. Koekemoer; Mbavhalelo B. Shandukani; Delenesaw Yewhalaw; Basil D. Brooke (South African Journal of Science)
Owing to the scarcity of malaria vector mosquito populations in urban settings, urban malaria is rare in South Africa. Anopheles stephensi, an efficient urban malaria vector in South Asia and parts of the Arabian Peninsula (excluding southwest Saudi Arabia and Yemen), has recently expanded its range into African countries and territories where it has not previously occurred. The central hypothesis to explain the recent dispersal of An. stephensi out of its endemic range and into sub-Saharan Africa is via shipping, making seaports especially vulnerable to introductions of this species, although land crossings and general population movements are likely important as well. Based on an analysis of global shipping networks, South Africa is at risk of invasion by this species, although it has not been recorded in southern Africa to date. The World Health Organization has issued an alert for the spread of An. stephensi, including guidelines for surveillance in non-invaded areas, territories or countries that could be at risk. The aim of this review was to assess the risk of An. stephensi to South Africa and provide recommendations for vigilance and vector surveillance. We conclude that the range expansion of An. stephensi poses a significant threat to malaria control and elimination in southern Africa, and recommend regularised surveillance in at-risk areas, further engagement with existing multisectoral and cross-border initiatives, the mitigation of malaria in urban planning, and community awareness concerning water storage practices.